VIRTUAL UNIVERSITY OF ADULT EDUCATION - PROSPECTS OF TRANSITION TO A NEW MODEL OF POSTGRADUATE EDUCATION: adult education; digitalization of education; digital technologies; open education; postgraduate education; virtual university - Deineha, Iryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The modern transformation of society on the path to digital inevitably requires qualitative changes in all areas of its operation, especially in education. The relationship between the university and society is increasingly becoming a business relationship, which leads to the development of the relationship "supply and demand" and forces universities to change and improve ways of providing educational services and anticipate the demands of their customers. The purpose of scientific research is to study the implementation of the paradigm of open education in Ukraine and the prospects for the transition of postgraduate education to a new model - a virtual university of adult education. This will help to solve the problem of equal access to quality postgraduate education, which must meet the needs of modern society. The basic concepts of the research are considered, namely: "open education", "open educational environment", "virtual university" and the author's vision of their relationship is presented. The advantages of the activity of virtual universities are described and the foreign and domestic experience of their functioning is presented. The study was conducted using the bibliographic method, the method of structural-scientific analysis, comparison and systematization. This allowed to determine the feasibility of maximum use in the educational process of adult modern digital technologies, the implementation of training on the basis of a virtual university. Result. It is determined that the work of virtual universities is pedagogically, economically and socially expedient, and therefore should be a priority of public policy in the field of higher education in general and postgraduate in particular. Virtual University of Adult Education should become a new model of postgraduate education. Conclusions. The implementation of the concept of lifelong learning has a positive impact on economic growth and competitiveness of the country in the high-tech market and acts as a catalyst for reforming education in general. Modern human must not only adapt to new conditions, but also be effective in his professional activities, be the initiator of activity, the subject of life and work. For a partial solution to this problem, virtual universities are effective, which have already confirmed the pedagogical, economic and social feasibility of their creation and operation. Examples of their positive functioning are in foreign countries, the experience of their activities is observed in Ukraine